Fast-growing broiler chickens range more in a silvopasture than a grass pasture based on live observations - Jacobs, Leonie; Paneru, Bidur; Brooks, George C.; Downing, Adam K.; Munsell, John F.; Fike, John H.; Pent, Gabriel (Frontiers in Animal Science, 2026)
Broiler chickens with free-range access often show low use of the outdoor space and providing access to a silvopasture (intentional integration of vegetation and animal production) may increase range use. The study aim was to evaluate the effect of pasture system (silvopasture; open grass pasture) on range use in fast-growing broiler chickens. Fifty-three or 54 birds per experimental unit in two experiments were provided access to 125m2 silvopasture plots (x̄ 32% canopy cover) or open grass pasture plots (no canopy cover) from day 24 of age. Plot-level range use (% of the flock outside) was assessed from photographs for 16 days in Experiment 1 and 18 days in Experiment 2. In Experiment 2, live observations of range use were performed on days 29, 30, 34, 35, 40, and 41. We used generalized linear mixed models to predict broiler ranging activity at different times of day (morning, midday, afternoon) as a function of average daily temperature, bird age, and pasture treatment. Younger birds were more likely to range on cold days, while older birds ranged more on warm days, consistent across live observations and photographs. Live observations showed more birds in silvopastures than open pastures, whereas photographs indicated the opposite. Bird counts may be underestimated in the photos, due to visual obstruction by vegetation, especially in the silvopastures. The contrasting outcomes highlight that the choice of sampling method strongly influences conclusions about range use. Consistent across photographs and live observations, range use followed a diurnal rhythm, with highest use in mornings and afternoons. Overall, silvopasture provided age- and temperature-dependent benefits for broiler chickens, highlighting the importance of giving birds the choice to range outdoors or remain indoors.